Biomechanics and analysis of running gait - Dugan, S. A.; Bhat, K. P. (Physical Medicine & Rehabilitation Clinics of North America, 2005)
Summary: Physical activity, including running, is important to general health by way of prevention of chronic illnesses and their precursors. To keep runners healthy, it is paramount that one has sound knowledge of the biomechanics of running and assessment of running gait. More so, improving performance in competitive runners is based in sound training and rehabilitation practices that are rooted firmly in biomechanical principles. This article summarized the biomechanics of running and the means with which one can evaluate running gait. The gait assessment techniques for collecting and analyzing kinetic and kinematic data can provide insights into injury prevention and treatment and performance enhancement.